The Effect of Using Listen and Draw and Dictogloss Technique on Students’ Ability in Listening Comprehension at the Tenth Grade of SMA Negeri 1 Lahewa - Agustinus Gea; Erika Sinambela; Arsen Nahum Pasaribu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Listening is an important skill that should be mastered by the students in the classrooms since the skill involves a process of understanding spoken message. The pupose of this research is to identify the students’ ability in listening skill. The research was done through quasi experimental design. The population of the research was tenth grade students of SMA Negeri 1 Lahewa which consisted of 150 students while the samples were class X-MIA1 as the experimental group A and X-MIA4 as the experimental group B which consisted 60 students. The data were taken by using instrument or test. After validating the test, the researcher gave the pre-test to both classes to examine the normality of the data. The students’ mean score result in pre-test of the experimental group A was 71.83 and for the experimental group B was 66.33. Both are categorized adequate. After giving the treatment, the researcher administered the post test in both of the classes to get the result of the treatment and to examine the result of the normality of the data and homogeneity. Based on the result of the data computation of experimental group A, the mean score was 82.16 and for the experimental B was 75.16 classified good. Based on the result of hypothesis by using t-independent, the researcher got tcount = 2.2435 ≥ ttable = 2.0115 with dk = 2(n-1) = 2(30-1) = 58 and the significance level is 5% (α = 0.05). It means, Ha was accepted and Ho was rejected. It can be concluded that there is a significant effect of Using Listen and Draw and Dictogloss Technique on the students’ listening skill at the Tenth Grade of SMA Negeri 1 Lahewa.